Magnetization performance of BP-Based algorithm - Abdelhedi, Manel; Hamdi, Omessaad; Bouallegue, Ammar (Melecon 2010 - 2010 15th IEEE Mediterranean Electrotechnical Conference, 2010)
In this paper, we present the performance of the Belief Propagation-Based (BP-Based) algorithm as a function of the magnetization. Previous works, have shown that the BP algorithm, is equivalent to the Thouless- Anderson-Palmer(TAP) approach, we develop the log-likelihood ratios-Belief Propagation (LLR-BP) algorithm and its simplification, the BP-Based algorithm using this method.